Classifying research groups in the Orinoquia region: the objective is not just to get there but rather in staying there (2009)
ABSTRACT: The results of the recent research group classification during the past Colciencias meeting for such purpose in 2008 revealed a significant increase in institutional research capacity, rising from 2 to 11 groups recognised by the Universidad de los Llanos and another 10 belonging to other institutions.